Fatty acid profiles reveal dietary variability of a large calanoid copepod Limnocalanus macrurus in the northern Baltic Sea. - von Weissenberg, E., H. Ruhanen, M. Holopainen, R. Käkelä & J. Engstroem-Öst (Frontiers In Marine Science, 2024)
Eutrophication, climate-induced warming, and salinity fluctuations are altering the fatty acid profiles and the availability of essential polyunsaturated fatty acids (PUFAs) in marine zooplankton communities. Limnocalanus macrurus Sars G.O., 1863 is a large calanoid copepod inhabiting the low-salinity areas in the Baltic Sea, where it is a major source of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) to commercially important fish. L. macrurus is sensitive to warming, eutrophication and hypoxia. As an opportunistic feeder, it is capable of dietary shifts, which affects its fatty acid profiles. Although much studied in boreal lakes, there are only a few studies on the fatty acid profiles of the Baltic Sea populations. This study aimed to compare the fatty acid profiles of L. macrurus in three basins of the Baltic Sea, in relation to the community fatty acids and environmental variables. We collected samples of L. macrurus and filtered plankton community for gas chromatographic fatty acid analyses in August 2021 on R/V Aranda. The nutritional quality of L. macrurus to consumers was lower in the Gulf of Finland (GoF) compared to the Gulf of Bothnia, indicated by the low levels of DHA and EPA, as well as the low n-3/n-6 ratio of PUFAs. The lower ratio of 18:1n-7 to 18:1n-9 implied higher degree of omnivory in GoF. In contrast, a diatom marker 16:1n-7 had high proportion in the Bothnian Bay. High temperatures in GoF may have restricted feeding in the upper water column, possibly forcing a shift towards cyanobacteria or seston-based diet, as interpreted from a high proportion of 18:2n-6 and 18:3n-3. We conclude that the ability of L. macrurus to utilize multiple food sources increases its resilience to environmental change, while the consequences on the nutritional quality may have further cascading effects on the food webs.